Language variables in administrative health data hosted at ICES - Batista, Ricardo; Prud'homme, Denis; Tanuseputro, Peter; Manuel, Doug (L'institut du Savoir Monfort and ICES Ottawa, 2019)
Research on linguistic minorities have revealed important disparities in Canada. Numerous analyses have identified the need for further studies looking at health status, healthcare utilization access barriers and quality of care affecting francophone living in a minority contexts (FLMCs) in Canada.1 The value and need to improve access and use of valid health information to support the planification of health and social services is well documented; however, important gaps and challenges have been recognized, which limit further progress in understanding the disparities in health and health care for some subpopulations. 2